2014
DOI: 10.1002/jssc.201301037
|View full text |Cite
|
Sign up to set email alerts
|

Rapid determination of natural and synthetic hormones in biosolids and poultry manure by isotope dilution GC–MS/MS

Abstract: The release of hormones into the environment due to land application of biosolids and manure is a cause of concern for their potential impacts. This paper presents the development of a rapid and sensitive method, based on extraction, for the analysis of 13 hormones in biosolids and poultry manure. A simultaneous derivatization of hydroxyl and ketone groups was carried out for the determination of hormones by GC–MS/MS. The method was validated in three matrices (sewage sludge, manure, and broiler litter). Recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…As shown in Table 1, seven and six steroids were detected in the swine feces (5.3e3300 ng/g) and chicken feces (4.9e2200 ng/g), respectively, which were lower than those detected in swine feces from livestock farms (<LOQ to 8100 ng/g) (Liu et al, 2012b). Six steroids were detected in geese feces samples (2.0e85 ng/g), which were lower than those detected in poultry litter (ND to 321 ng/g) (Albero et al, 2014). The differences among these feces samples may be due to different excretion ratio and usage of steroids in these animals.…”
Section: Steroids In the Feces Samplesmentioning
confidence: 80%
See 1 more Smart Citation
“…As shown in Table 1, seven and six steroids were detected in the swine feces (5.3e3300 ng/g) and chicken feces (4.9e2200 ng/g), respectively, which were lower than those detected in swine feces from livestock farms (<LOQ to 8100 ng/g) (Liu et al, 2012b). Six steroids were detected in geese feces samples (2.0e85 ng/g), which were lower than those detected in poultry litter (ND to 321 ng/g) (Albero et al, 2014). The differences among these feces samples may be due to different excretion ratio and usage of steroids in these animals.…”
Section: Steroids In the Feces Samplesmentioning
confidence: 80%
“…Previous studies paid their attention to the detection of steroids in animal feces in single culture system such as swine farms, cattle farms or chicken farms (Albero et al, 2014;Liu et al, 2012bLiu et al, , 2015c, but few studies reported the concentrations of steroids in polyculture system as farm F1. As shown in Table 1, seven and six steroids were detected in the swine feces (5.3e3300 ng/g) and chicken feces (4.9e2200 ng/g), respectively, which were lower than those detected in swine feces from livestock farms (<LOQ to 8100 ng/g) (Liu et al, 2012b).…”
Section: Steroids In the Feces Samplesmentioning
confidence: 99%
“…10 Microextraction techniques have become a developing research interest due to the simplicity and small sample and solvent volumes associated with them. 10,[26][27][28] QuEChERS method is chosen by many research groups due to its simplicity. [15][16][17][18][19] Molecularly imprinted sorbents enables the selective extraction of analytes, enhancing the efficiency of extraction process while eliminating additional clean-up steps.…”
Section: Extraction Methods Of Steroidal Estrogensmentioning
confidence: 99%
“…They can influence and regulate organism growth, metabolism, cell division and differentiation, leaf morphologies, and senescence . Up to date, several methods have been reported for the detection of phytohormones, including spectroscopy , CE , CE–LIF , impedance immunosensor , GC–MS , HPLC , nano‐HPLC–MS/MS , HPLC–MS/MS , and UHPLC–MS/MS . Among them, spectroscopic methodology has the lowest accuracy.…”
Section: Introductionmentioning
confidence: 99%